Best orthogonal trigonometric approximations of the classes B^Ω_p,θ of periodic functions of many variables - Voitenko, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain exact-order estimates for the best orthogonal trigonometric approximations of the classes B^Ω_p,θ of periodic functions of many variables in the space L_q.